Integrative strategies for the K-12 social studies classroom - Lintner, Timothy (Teaching and learning social studies., 2013)
While the concept of integration or an interdisciplinary curriculum has been around for decades, the purposeful practice of integration is a relatively new educational endeavor. Though classroom teachers often say they "integrate," there generally seems to be a lack of understanding of what this thing called integration is (theory) and what it is supposed to look like in the classroom (practice).Arguably, no other discipline has felt the pressure to integrate more than social studies. Marginalized by federal initiatives such as No Child Left Behind and suffering from a general crisis of credibility, social studies has been pushed further and further to the proverbial back burner of educational importance. Yet regardless of perspective or position, social studies remains ripe for integration.The crux of this book is to provide educators insights and strategies into how to integrate social studies with other discipline areas. Calling upon national experts in their respective fields, each chapter chronicles the broad relationship between individual content areas and social studies. Multiple examples of integrative opportunities are included. At the end of each chapter is a series of grade-specific integrative lesson plans ready for implementation. This book was purposefully designed as a how-to, hands-on, ready-reference guide for educators at all stages and all levels of teaching.